Lesbian Parenting Experience: An Examination of Cultural Socialization Practices and Child Rearing Strategies Amongst Lesbian Mothers in Thailand - Kumar, Sudawan; Pawle, Reginald H. (Scholar: Human Sciences, 2021)
An increasing number of lesbians in Thailand have entered parenthood, some through the context of formal heterosexual marriage, others through adoption and artificial insemination. As same-sex marriage is illegal in Thailand, accurate statistics have been difficult to acquire on the number of lesbian households. This qualitative study explores the experience of Thai lesbian parents who are within the empty spaces of Thai society, with little or no social and legal support. Seven lesbian parents from six provinces across Thailand were recruited and semi-structured interviews were conducted in this study. Thematic analysis was used to identify emerging themes and critical ethnography was used to expose challenges that resulted from social-political processes of unfairness and injustice. The results indicated that the participants adapt by finding ways to navigate and negotiate these social-political processes. They survive by reinventing, redefining their lives and challenging boundaries and choices that arise from being LGBT. The issues that they struggle with are both specific and non-specific to being LGBT. Through this, Thai lesbian parents continue to celebrate their diverse families which are normal yet different.